Rationalizing the value premium in emerging markets - Ebrahim, M. Shahid; Girma, Sourafel; Shah, M. Eskandar; Williams, Jonathan (Elsevier, 2014)
We reconfirm the presence of value premium in emerging markets. Using the Brazil–Turkey–India–China (BTIC) grouping during a period of substantial economic growth and stock market development, we attribute the premium to the investment patterns of glamour firms. We conjecture based on empirical evidence that glamour firms hoard cash, which delays undertaking of growth options, especially in poor economic conditions. Whilst this helps to mitigate business risk, it lowers market valuations and drives down expected returns. Our evidence supports arguments that the value premium is explained by economic fundamentals rather than a risk factor that is common to all firms.